Exploring Students’ Perceptions and Motivation in Using Quizizz for Grammar Program: A Study in Kampung Inggris Pare Kediri - Muhammad, Muhammad; Muchyidin, M Syaichul; Asyar, Wildan Isna; Naf’ihima, Fika Ar-rizqi (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2024)
This study investigates students’ perceptions of and motivation towards using Quizizz for grammar learning at Kampung Inggris Language Center in Pare Kediri. Using a quantitative descriptive method, data were collected through online surveys from 58 students. The study aimed to assess whether Quizizz, as a gamified learning tool, could enhance students’ engagement and motivation in grammar instruction. The results revealed that 96% of students found Quizizz easy to use and accessible, while 97% agreed that its gamification features, such as leaderboards and immediate feedback, made grammar lessons more engaging. Additionally, 93% of students reported that these features improved their overall learning experience. These findings highlight the potential of Quizizz to address motivational challenges and make grammar learning more interactive and enjoyable, particularly in non-formal educational settings like Kampung Inggris. By demonstrating the effectiveness of gamified learning tools, this research contributes to the understanding of technology integration in language instruction. It suggests that applications like Quizizz can foster both cognitive and affective engagement, potentially influencing broader educational practices.